Nutritional contribution of Coula edulis B. and Tetracarpidium conophorum M. A. to the Cameroon food composition table - Talla Tagne Naccis; Kotue Taptue Charles; Fokou Elie (Food Chemistry Advances)
Several nutrient-rich resources of agrobiodiversity are underutilized or unknown and remain underexploited. This study aimed to determine the nutritional properties of Coula edulis (CE) and Tetracarpidium conophorum (TC), two non-timber forest products from Cameroon. Samples were analyzed using standard methods. TC was separated into two batches: one raw (TCNT) and the other precooked (TCPT) before analysis. The proximate results analysis showed that CE was significantly (p ≤ 0.05) higher in total sugar, total fiber and vitamin C. TCNT had significantly (p ≤ 0.05) the highest protein content while TCPT the highest fat content (40.121±0.2). The highest levels of lycopene, β-carotene and vitamin A were significantly found in TCPT. CE and TCPT could cover respectively 56.45 % and 31.35 % of the population's nutritional references in vitamin C and vitamin A. The anti-nutritional compounds had contents significantly (p ≤ 0.05) lower than the safety threshold. The mineral profile revealed the presence of ten minerals. The most abundant mineral were K followed by Ca in CE only. Fe was also higher in CE. All these samples had high energy values. These data obtained from Coula edulis and Tetracarpidium conophorum could be used to further enrich cameroonian food table composition.